Changing socio-economic conditions of the resettled Khmu Rok ethnic group in Lao PDR - Sanhti Douangchanh; Ahmad, Mokbul Morshed; Routray, J ayant Kumar; Kusakabe, Kyoko; Sweden (Sida) (Pathum Thani, Thailand : Asian Institute of Technology, 2006)
This research inquired into the changes in socio-economic conditions of the resettled Khmu Rok ethnic group in 1999, Lao PDR. It first studies the change in economic conditions of the Khmu Rok. It then studies the changes in social conditions including integrations and conflicts among them with the Lao. It also studies the changes in the lives of Khmu Rok women and finally makes recommendations for further improvement of the situation. Data and information were collected through using the total of 39 sample household survey and multiple case studies of annual household incomes and expenditures, domestic violence and divorce. The research applied both qualitative and quantitative analysis. The study shows that the Khmu Rok's village resettlement had created a number of changes with both positive and negative impacts on their ways of life. With more access to formal education, public health, markets and employment opportunities, conversely, increase of rice insufficiency; domestic violence and divorce were also emerged. Changes of the cultural and traditional beliefs, land holding size, rice cultivation and livelihood practices. The complex issue of less agricultural land, rice insufficiency, unawareness on the Family Law and Law on Development and Protection of Women, losing the traditional and cultural beliefs and gender awareness warrant attention from government and donors
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Science in Regional and Rural Development Planning
Thesis (M.Sc.) - Asian Institute of Technology, 2006
Keywords: Khmu' (Southeast Asian people) -- Laos -- Economic conditions; Khmu' (Southeast Asian people) -- Laos -- Social conditions